Urban Population Growth and Job Opportunities: The Case of Albania - Ҫurçija Mario; Bejleri, Emirjeta (Naše gospodarstvo/Our economy, 2020)
Demographic change is a complex phenomenon, but it has generally been ac- cepted that having better employment opportunities and quality of jobs are among important factors that determine people’s mobility. The purpose of this paper is to test the relationship between the increase in the number of people living in urban areas and the job opportunities in these areas in Albania. In order to do so, we performed a statistical analysis of a dataset on labor force surveys for the time period of 2007-2013. Our findings confirmed a positive correlation between the increase of individuals living in a certain area and job opportuni- ties for specialized occupations in that area; however, a significant relationship was not found when job opportunities in general, in general, were considered.